Estimation of Heterosis and Inbreeding Depression for Fruit Yield Attributing Characters in Brinjal (Solanum melongena L.) - Mahla, Jagruti S.; Acharya, R. R.; Pandya, M. M.; Kumar, Sushil; Patel, D. A.; Parmar, D. J. (International Journal of Economic Plants, 2025)
The present investigation on generation mean analysis of brinjal was conducted in Anand (388110), Gujarat, India, from September to March 2023–2024 to study heterosis and inbreeding depression for yield traits. The observations were recorded on thirteen traits such as days to first flowering, branches per plant, plant height, leaf blade length, leaf blade width, fruit length, fruit girth, fruit length/girth ratio, fruits per plant, fruit yield per plant, total soluble solids and shoot and fruit borer incidences. The experimental material consisted of twelve basic generations viz., P1, P2, F1, F2, B1, B2, B11, B12, B21, B22, B1S and B2S of four families of brinjal namely, AB 20-19 × GAOB 2, AB 20-13 × CO 2, Anand Harit × GJB 3 and GPBRJ 204×Arka Harshitha. The results revealed that all four families exhibited positive and significant heterobeltiosis for plant height, leaf blade length, leaf blade width, fruit length, fruit girth, fruit weight and fruit yield per plant. The families AB 20-19 × GAOB 2 and GPBRJ 204×Arka Harshitha showed promising results for fruit yield per plant and its component traits, along with early flowering. The positive significant heterosis over the mid-parent and better parent, coupled with negative inbreeding depression, can be attributed to the major contribution from dominance (h) and additive × additive (i) gene effects. The family exhibiting the least inbreeding depression and high heterosis should be further explored for commercial production.